The Effect of Caffeine on Concentration and Accuracy of Archery (Universitas Negeri Semarang, 2022)
Caffeine is an active component. Some studies found that caffeine significantly enhances exercise performance, by increasing substrate distribution, heart rate, and oxygen absorption. This study aims to know the effect of caffeine on accuracy and concentration in archery. Participant in this study are 12 archers in Klaten city were active since 2019. The quasi-experimental with the one-group pretest-posttest design was used in this study. The data taken was accuracy and concentration (measure with archery scoring and Grid Concentration test) instrument before and after an intervention. The intervention was the participant drink caffeine in 2 grams/100 ml Robusta Coffee with ice (5°C - 10°C) and hot (65-70°C) temperature within 45 minutes before the performance. Paired t-test and wilcoxon was used to analyze the data.The result showed that the accuracy was significantly different between pre-test and post-test in both temperatures (cold, p = 0,003 and hot, p = 0,034). The concentration also showed different between pre-test and post-test (Cold, p = 0,010) and Hot, p = 0,004).This study concludes that consumption caffeine 45 minutes before archery performance increased accuracy and concentration in Archer.